Bridging The Digital Divide: Methodological Strategies For Conducting Remote Urban Research - Ahrar, Sana; Staub, Alexandra (Enquiry The ARCC Journal for Architectural Research, 2025)
This article examines methodological approaches for conducting community-engaged research remotely with participants who have limited internet access. Community-based urban research must include the voices of all stakeholders to ensure representation and equitable decision-making. The digital divide, characterized by varying levels of digital literacy and limited access to technology, often excludes disadvantaged stakeholder groups from remote data collection. While extensive studies have been conducted on both analog and digital data collection methods, few have focused on adapting these approaches to include digitally marginalized groups in architecture and urban studies. This article reflects on data collection adaptations made to bridge the digital divide in a project that was designed before, but conducted during, the COVID-19 pandemic, between November 2020 and May 2021. Grounded in a mixed-income, informally developed settlement in India, the study aimed to examine how residents in informal settlements met their social and recreational needs. The pandemic lockdowns made on-site data collection infeasible, prompting the research to be adapted for remote implementation using a mixed-methods approach tailored to participants’ levels of digital literacy and access. Multiple strategies were employed to collect representative data and ensure data validity, including online and telephone-based surveys, telephone interviews, and participant-generated visual data. Residents with phone and internet access were employed as intermediaries to help navigate trust and accessibility challenges and to recruit participants without digital access. In addition to presenting the study’s remote data collection methods, this article also identifies ethical challenges that may arise when using intermediaries to bridge the digital divide in qualitative research where the researcher is not physically present.